The Kronecker Summation Method for Robust Stabilization Applied to a Chemical Reactor - Radek Matušů; Jana Závacká; Roman Prokop; Monika Bakošová (Journal of Control Science and Engineering)
The paper focuses on robust stabilization where the suitable parameters of a simple continuous-time PI controller are determined through a combination of the Kronecker summation method, sixteen plant theorem, and an algebraic approach to control design in the ring of proper and stable rational functions. The initial theoretical background is followed by an illustrative experiment which includes computation of the controller and verification of control results for a continuous stirred tank reactor with exothermic reaction modelled as a fourth-order interval system.